(untitled) (Washington, 2010)
Volume 2 explores needs and draws experience from region-specific contexts and detailed case studies. The case studies describe how drivers and consequences of change play out in specific geographical areas, and how public and private responses are shaped and implemented.
Keywords: Livestock systems,Hệ thống chăn nuôi; Environmental aspects,Khía cạnh môi trường